2005
DOI: 10.1021/ma047923p
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Responsive Behavior of Elastin-Based Side Chain Polymers

Abstract: Linear poly(VPGVG) has been extensively studied over the years as a model for the structural protein elastin. Elastin is characterized by a lower critical solution temperature (LCST). This LCST can be influenced by several factors, mainly molecular weight, concentration, and pH. An ABA type block copolymer was synthesized using atom transfer radical polymerization (ATRP), in which the VPGVG sequence is in the side chain of the A block and the B block is poly(ethylene glycol) (PEG). The LCST behavior of this se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
112
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 25 publications
7
112
0
2
Order By: Relevance
“…Ayres et al prepared a block copolymer with a central poly ethylene glycol (PEG) chain and polymethacrylate fl anking blocks whose side chains were functional with Val-Pro-Gly-Val-Gly. These hybrid materials maintained an LCST behaviour as they displayed a similar coacervation behaviour as tropoelastin [133]. Amino acid residues in the main chain of a linear elastin polypeptide have also been functionalised with methacrylate in order to obtain a photocrosslinkable site [168].…”
Section: Fusion Proteinsmentioning
confidence: 99%
“…Ayres et al prepared a block copolymer with a central poly ethylene glycol (PEG) chain and polymethacrylate fl anking blocks whose side chains were functional with Val-Pro-Gly-Val-Gly. These hybrid materials maintained an LCST behaviour as they displayed a similar coacervation behaviour as tropoelastin [133]. Amino acid residues in the main chain of a linear elastin polypeptide have also been functionalised with methacrylate in order to obtain a photocrosslinkable site [168].…”
Section: Fusion Proteinsmentioning
confidence: 99%
“…Yet, several other macromolecules exhibit a LCST in aqueous medium. For instance, three important alternative classes of thermoresponsive polymers have been identified during the last ten years: elastin-like polypeptides [8,9], poly(alkyl oxazolines) [10][11][12] and polymers with short oligo(ethylene glycol) side-chains [13]. The latter family is composed of different sub-classes.…”
Section: Introductionmentioning
confidence: 99%
“…25 Several examples in which peptide sequences are incorporated into polymer chains have been shown to control the material properties and enable self-assembly into well-defined nanoscale architectures. [26][27][28] Besides proteins, this could also apply to nucleobase block copolymers. In previous investigations, it already has been demonstrated that the incorporation of small oligonucleotide strands has vast potential to influence the aggregation of block copolymers.…”
Section: Introductionmentioning
confidence: 99%